2017
DOI: 10.1126/scisignal.aai8026
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation-dependent regulation of MDM2 E3 ligase activity dictates its oncogenic function

Abstract: Abnormal activation of the oncogenic E3 ubiquitin ligase murine double minute 2 (MDM2) is frequently observed in human cancers. By ubiquitinating the tumor suppressor p53 protein, which leads to its proteasome-mediated destruction, MDM2 limits the tumor-suppressing activity of p53. On the other hand, by ubiquitinating itself, MDM2 targets itself for destruction and promotes the p53 tumor suppressor pathway, a process that can be antagonized by the deubiquitinase herpesvirus-associated ubiquitin-specific protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 46 publications
1
57
0
Order By: Relevance
“…Ras-ERK signalling could degrade PKA by regulating MDM2, indicating Ras-ERK inhibited PKA in a proteasome-dependent manner. It is well-known that MDM2 plays a significant role in proteasome-mediated degradation [18]. However, whether MDM2 directly inhibited PKA function or by mediating other factors are still unclear, which needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ras-ERK signalling could degrade PKA by regulating MDM2, indicating Ras-ERK inhibited PKA in a proteasome-dependent manner. It is well-known that MDM2 plays a significant role in proteasome-mediated degradation [18]. However, whether MDM2 directly inhibited PKA function or by mediating other factors are still unclear, which needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Further, how PKA was degraded by Ras-ERK signalling was studied. Considering MDM2 is a widely known protein in driving proteasome-mediated degradation [18], we focused on MDM2 for further investigation. Results in Figure 6(A,B) revealed that transfection of cells with an MDM2 expression vector (MDM2-His) remarkably repressed the endogenous and exogenous protein levels of PKA.…”
Section: Ras-erk Pathway Degrades Pka Through Modulation Of Mdm2mentioning
confidence: 99%
“…Degradation processes in the p53 pathway add additional layers of complexity because several p53-targeting E3 ligases, including MDM2 and COP1, also have autoubiquitination activity (140,141). Furthermore, genes encoding the E3 ligases COP1, MDM2, PIRH2, and JFK, all of which target p53, are induced by the transcriptional activity of p53 (138,139,(142)(143)(144).…”
Section: P53 Pathwaymentioning
confidence: 99%
“…In mouse, the corresponding residues are K 130 and K 140 (mouse Siah2 GenBank: NP_033200.2). E3 ubiquitin ligase function depends on the acetylation of the "really interesting new gene" domain (23,35). Therefore, we examined the effects of acetylation-null mutations at K 129 and K 139 of Siah2.…”
Section: H Pylori Increases Acetylation Of Siah2 In the Infected Gccsmentioning
confidence: 99%
“…In hypoxia, PHD3 is targeted for degradation by Siah2 (22). It has been recently reported that the function and stability of the E3 ubiquitin ligase mouse double minute 2 are tightly regulated by p300-mediated acetylation (23), wherein acetylation results in reduced self-ubiquitination-mediated degradation of mouse double minute 2. However, the effect of acetylation in regulating Siah function and H. pylori pathogenesis is unknown.…”
mentioning
confidence: 99%